2014
DOI: 10.1007/s12205-013-0597-1
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance evaluation of low cost Earth to air heat exchanger model suitable for small buildings in arid and semi arid regions

Abstract: An experimental study was performed on a prototype model of Earth to Air Heat Exchanger System (EAHE) equipped with low cost material like PVC pipes and exhaust fans made on temporary platform. Emphasis was given on the design of the duct system suitable for small houses without any space in urban and rural areas. Tests were performed to predict the cooling potential and impact of the material on the performance of EAHE system. Experiment was performed continuously for more than three weeks and the result show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The COPs of the systems utilizing underground air tunnels are much higher. For open and closed loop systems, the COP can be as high as 10 [33].…”
Section: B Application Of Earth Pipe Coolingmentioning
confidence: 99%
“…The COPs of the systems utilizing underground air tunnels are much higher. For open and closed loop systems, the COP can be as high as 10 [33].…”
Section: B Application Of Earth Pipe Coolingmentioning
confidence: 99%
“…These are the strong reasons for researchers to shift their attention from a real field experimental approach to a laboratory-scale experimental setup that has sufficient data, more controllable and robust conditions along with high experiment repetition chances. Mishra et al [46] performed an experimental test on a prototype model of EAHE appropriate for small homes made utilizing reasonably-priced material like PVC (polyvinyl chloride). After conducting the experiment for three weeks their results revealed that outlet temperature of air ranges between 20 • C and 22 • C, regardless of inlet air temperature ranging from 34 • C to 44 • C. Also, the minimum energy efficiency ratio became observed as 3.34 which is equivalent to a 5-star rating as per the Bureau of Energy Efficiency (BEE).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have investigated selected aspects of GAHE design and operation. Misra et al [16] proposed a solution for minimizing GAHE installation costs and maximizing energy gain. Baglivo et al [17] aimed to determine the optimal number of tubes in a horizontal GAHE by analyzing air temperature, air flow rate, pipe depth, and soil thermal conductivity in TRNSYS 17 software.…”
mentioning
confidence: 99%